EDUCAÇÃO, CIÊNCIA E DOUTRINAS RELIGIOSAS: RELAÇÕES E REPERCUSSÕES PARA AS ESCOLAS PÚBLICAS - Cruz, Renata Barbosa da (2015)
This study investigates the relations and the repercussions in the public schools, of the scientific contents and the doctrinal orientations from Christian denominations, both Catholic and Evangelical groups. These impacts mainly occur in relation to two themes: 1) sexual and reproductive rights and gender issues; 2) Creationism versus Evolutionism. The methodology used consisted of a qualitative research, documentary, consisting of content analysis and literature review. The documentary research had been made using the Google engine search, during the period from August 2011 until September 2014. After surveying some of the countless religious websites and blogs, it was possible to selected 28 texts, which were published in 11 websites and 5 blogs, from 9 different Christian groups. Those groups are: Assembleia de Deus, Igreja Adventista do Sétimo Dia, Igreja Universal do Reino de Deus, Testemunhas de Jeová, Igreja Evangélica de Confissão Luterana no Brasil (IECLB), Igreja Batista Lagoinha, Igreja Evangélica Cristã, Igreja Presbiteriana do Brasil and Igreja Católica Apostólica Romana. The results of the analysis of these texts enabled a better understanding of some points of view and doctrinal relations in connection to the researched themes. The Christian religious denominations that addressed the Creationism and the Evolutionism theme, presented a contrary view of the Theory of Evolution by Charles Darwin, thus stated that the scientific theories around the origin of the world and the species are conflicting with the Creationism. In relation to the sexual and reproductive rights and the gender issues, the analyzed texts have shown, mostly, a contrary positioning to homosexuality, contraception, having an abortion and the sexual intercourse before the matrimony. Such texts when checked out to some of the scientific contents proposed by the Ministry of Education, allowed to confirming the proposed hypothesis, that it is possible to identify repercussions of religious doctrines interfering in public schools work referring scientific contents.